2021
DOI: 10.15376/biores.16.1.wei
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystal-based liquid crystal structures and the unique optical characteristics of cellulose nanocrystal films

Abstract: Liquid crystals (LC) have been found to have many unique characteristics during the last few decades. The liquid crystal phase is ubiquitous in the biological world, as well as in cellulose and its derivatives. Cellulose nanocrystals (CNC), which can obtain the chiral LC phase in aqueous suspension, have been attracting much attention. The unique size and properties of CNC, such as their light weight, special optical properties, non-toxicity, and biocompatibility, etc., have made them widely applicable in dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…This helix structure can be maintained in the dried film through the slow evaporation of water [17]. Thus, the CNC solid film can exhibit unique optical properties, and when the incident light wavelength is in the visible range, the material appears colorful to the naked eye [18,19]. To date, the research on this optical film has aroused far-ranging interest, such as in optical anti-counterfeiting, sensors, and some composite devices [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This helix structure can be maintained in the dried film through the slow evaporation of water [17]. Thus, the CNC solid film can exhibit unique optical properties, and when the incident light wavelength is in the visible range, the material appears colorful to the naked eye [18,19]. To date, the research on this optical film has aroused far-ranging interest, such as in optical anti-counterfeiting, sensors, and some composite devices [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was found that the CNC suspension could form a film after drying (Figure S9, Supporting Information). However, the nanoscale size and strong hydrophilicity of CNC fibers leaded to poor strength and usability of the CNC film. Many studies have targeted to improve its hydrophobic properties. In this section, the properties of the composite film formed by the dispersion of CNC loaded with CDs in the UV resin were discussed (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…However, its application was questioned due to the presence of phenolic resin, which was easily oxidized and yellowing, but this did not prevent it from providing a new strategy for the construction of cellulose-based materials. CNC is a green nanomaterial with excellent mechanical properties, high crystallinity, and what is more, CNC suspension in a specific range of length-diameter ratio can form cholesteric liquid crystal. This kind of material has special optical properties such as selective light reflection, strong optical rotation, etc., which makes it an excellent candidate to construct optical management function composite material …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for CNCs, when exceeding the critical concentration, they will spontaneously organize into chiral nematic lyotropic LCs [257] by stacked layers of oriented CNC spindles. In addition, when the pitch of CNCs is compared to the wavelength of visible light, the thin films can selectively reflect LCP light and appear iridescent color, which can be applied in optical filters, solar gain regulators, [258][259][260] and stimuli-responsive stretchable optics. [254] Gao et al [261] built a luminophore-chiral CNC interface to obtain dual-mode CP light emission; thus, LCP and RCP can emit easily without applying any harsh condition.…”
Section: Cpl Based On Lyotropic Lcsmentioning
confidence: 99%